Fintech landscape in Sub-Saharan Africa - the case of Mozambique: a new savings alternative for the unbanked in Mozambique - Magalhães, Maria da Assunção da Cunha de (2022)
The lack of access to traditional finance makes Sub-Saharan Africa an attractive market for the adoption of FinTech services. This report provides an overview of Sub-Saharan Africa’s Fintech landscape, high lighting the case of Mozambique. By constructing a database of active fin techs in the region ,the report identifies top Fin tech verticals and countries. To assess the factors behind Fin Tech success, as coring model covering five pillars– regulation, demand, talent, capital and feeling of community–is also designed. These results served as the basis to explore the opportunities and challenges of Mozambique’s Fin Tech ecosystem and provide recommendations for its growth.